Proteomic Analysis of Exosome-Like Vesicles Isolated From Saliva of the Tick Haemaphysalis longicornis - Nawaz, Mohsin; Malik, Muhammad Irfan; Zhang, Houshuang; Hassan, Ibrahim A.; Cao, Jie; Zhou, Yongzhi; Hameed, Mudassar; Hussain Kuthu, Zulfiqar; Zhou, Jinlin (Frontiers in Cellular and Infection Microbiology, 2020)
Extracellular vesicles (EVs), are considered as vehicles of cellular communication. Parasites usually release EVs in their excretory-secretory products to modulate host environment. However, little is known about the secretion of EVs by ticks. In this study, we show for the first time that the tick, Haemaphysalis longicornis, secretes EVs, resembling exosomes. EVs were purified from saliva of partially engorged H. longicornis ticks. Electron microscopy analysis revealed the presence of exosome-like vesicles with a size of 100 nm. Proteomic analysis by LC-MS/MS identified a total of 356 proteins in tick-derived EVs. The presence of exosomal markers (CD63, Hsp70 and GAPDH) as well as parasite-specific proteins provided further confirmation of their release by the ticks. Bioinformatics analysis (Gene Ontology) indicated association of certain biological and molecular functions with proteins which may be helpful during tick development. Likewise, KEGG database revealed involvement of vesicular proteins in proton transport, detoxification, ECM-receptor interaction, ribosome, RNA transport, ABC transporters and oxidative phosphorylation. The results of this study provide evidence that EVs are being secreted by the ticks and suggest that tick-derived EVs could play important roles in host-parasite relationships. Moreover, EVs could be a useful tool in development of vaccines or therapeutics against ticks.